2018
DOI: 10.1016/j.trf.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Who buys New Energy Vehicles in China? Assessing social-psychological predictors of purchasing awareness, intention, and policy

Abstract: Who buys new energy vehicles in china? Assessing social-psychological predictors of purchasing awareness, intention, and policy. Transportation Research Part F Traffic Psychology and Behaviour, 58. pp. 56-69.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 74 publications
3
82
0
Order By: Relevance
“…Perceived behavioral control was defined in this study as assessing their self-perception of eases/difficulties in AV or SAV use intention. The perceived behavioral control has been also criticized as a significant predictor of behavioral intention in TPB model [54,62,65]. In the study, three items used to measure perceived behavior control had high factor loadings and appeared highly internal reliability (Cronbach's alpha = 0.908 for AV model and 0.907 for SAV model).…”
Section: Perceived Behavior Control and Its Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Perceived behavioral control was defined in this study as assessing their self-perception of eases/difficulties in AV or SAV use intention. The perceived behavioral control has been also criticized as a significant predictor of behavioral intention in TPB model [54,62,65]. In the study, three items used to measure perceived behavior control had high factor loadings and appeared highly internal reliability (Cronbach's alpha = 0.908 for AV model and 0.907 for SAV model).…”
Section: Perceived Behavior Control and Its Implicationsmentioning
confidence: 96%
“…Perceived behavioral control has the same ability as actual behavioral control, which will have a direct impact on behavioral intention. Related research have shown that perceived behavioral control is strong determinants of intentions to purchase new energy vehicles [54,65]. With regards to AVs, several constraints do exist.…”
Section: Perceived Behavioral Control (Pbc)mentioning
confidence: 99%
“…Regarding psychological factors, Du et al [38] have suggested that attitudes towards behavior, subjective norms, perceived behavioral control and personal norms are strong determinants of intention to purchase an EV. Qian [2] has deemed the use of sustainable products as compatible with a consumer's values and beliefs to be an important factor.…”
Section: Influential Factors To the Adoption Of Electric Vehicles (Evs)mentioning
confidence: 99%
“…Climate change poses many challenges for sustainable development and energy policy [1,2], and greenhouse gas emissions from human beings will exacerbate global climate change. Therefore, sustained reductions in carbon emissions are required from all sectors of the economy, including households and individuals.…”
Section: Introductionmentioning
confidence: 99%